2023
DOI: 10.1097/mcp.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

The association of preexisting severe asthma with COVID-19 outcomes

Abstract: Purpose of reviewThree years after the emergence of coronavirus disease 2019 (COVID-19), many studies have examined the association between asthma and COVID-related morbidity and mortality, with most showing that asthma does not increase risk. However, the U.S. Centers for Disease Control (CDC) currently suggests that patients with severe asthma may, nonetheless, be particularly vulnerable to COVID-19-related morbidity. Recent findingsWith respect to poor COVID-19 outcomes, our search yielded nine studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, ICS in previous studies have not shown a clear or consistent association with COVID-19 outcomes [66] , [67] , [68] . Given the immunomodulatory effects of ICS and the controversial results, Terry et al recently found that ICS use in asthmatics was associated with decreased mortality in COVID-19 [69] . The above mentioned explanations, to a certain extent, illustrated the relationship between asthma and lower risk for death from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, ICS in previous studies have not shown a clear or consistent association with COVID-19 outcomes [66] , [67] , [68] . Given the immunomodulatory effects of ICS and the controversial results, Terry et al recently found that ICS use in asthmatics was associated with decreased mortality in COVID-19 [69] . The above mentioned explanations, to a certain extent, illustrated the relationship between asthma and lower risk for death from COVID-19.…”
Section: Discussionmentioning
confidence: 99%